Ezetimibe for the treatment of nonalcoholic steatohepatitis: Assessment by novel magnetic resonance imaging and magnetic resonance elastography in a randomized trial (MOZART trial). Issue 4 (27th February 2015) - Loomba, Rohit; Sirlin, Claude B.; Ang, Brandon; Bettencourt, Ricki; Jain, Rashmi; Salotti, Joanie; Soaft, Linda; Hooker, Jonathan; Kono, Yuko; Bhatt, Archana; Hernandez, Laura; Nguyen, Phirum; et al.
Abstract : Ezetimibe inhibits intestinal cholesterol absorption and lowers low‐density lipoprotein cholesterol. Uncontrolled studies have suggested that it reduces liver fat as estimated by ultrasound in nonalcoholic steatohepatitis (NASH). Therefore, we aimed to examine the efficacy of ezetimibe versus placebo in reducing liver fat by the magnetic resonance imaging‐derived proton density‐fat fraction (MRI‐PDFF) and liver histology in patients with biopsy‐proven NASH. In this randomized, double‐blind, placebo‐controlled trial, 50 patients with biopsy‐proven NASH were randomized to either ezetimibe 10 mg orally daily or placebo for 24 weeks. The primary outcome was a change in liver fat as measured by MRI‐PDFF in colocalized regions of interest within each of the nine liver segments. Novel assessment by two‐dimensional and three‐dimensional magnetic resonance elastography was also performed. Ezetimibe was not significantly better than placebo at reducing liver fat as measured by MRI‐PDFF (mean difference between the ezetimibe and placebo arms ‐1.3%, P = 0.4). Compared to baseline, however, end‐of‐treatment MRI‐PDFF was significantly lower in the ezetimibe arm (15%‐11.6%, P < 0.016) but not in the placebo arm (18.5%‐16.4%, P = 0.15). There were no significant differences in histologic response rates, serum alanine aminotransferase and aspartate aminotransferase levels, or longitudinal changes in two‐dimensional and three‐dimensional magnetic resonance elastography‐derived liver stiffness between the ezetimibe and placebo arms. Compared to histologic nonresponders (25/35), histologic responders (10/35) had a significantly greater reduction in MRI‐PDFF (‐4.35 ± 4.9% versus ‐0.30 ± 4.1%, P < 0.019). Conclusions : Ezetimibe did not significantly reduce liver fat in NASH. This trial demonstrates the application of colocalization of MRI‐PDFF‐derived fat maps and magnetic resonance elastography‐derived stiffness maps of the liver before and after treatment to noninvasively assess treatment response in NASH. (Hepatology 2015;61:1239–1250)